2019
DOI: 10.3389/fvets.2019.00082
|View full text |Cite
|
Sign up to set email alerts
|

Early Nutrition Programming (in ovo and Post-hatch Feeding) as a Strategy to Modulate Gut Health of Poultry

Abstract: Healthy gastrointestinal tract (GIT) is crucial for optimum performance, better feed efficiency, and overall health of poultry. In the past, antibiotic growth promoters (AGP) were commonly used to modulate the gut health of animals. However, considering the public health concern, the use of AGP in animal feeding is banned or regulated in several jurisdictions around the world. This necessitates the need for alternative nutritional strategies to produce healthy poultry. For that, several alternatives to AGP hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 101 publications
1
99
0
2
Order By: Relevance
“…In other studies, the effect of antibiotics seems to be related to improving immune function of antibiotics rather than to its antibiotic effect (Attia et al 2017). Moreover, some reports showed that the functions of antibiotics might be related to the body in a sub-healthy state (Sugiharto 2016;Jha et al 2019). The specific mechanism needs further research.…”
Section: Discussionmentioning
confidence: 93%
“…In other studies, the effect of antibiotics seems to be related to improving immune function of antibiotics rather than to its antibiotic effect (Attia et al 2017). Moreover, some reports showed that the functions of antibiotics might be related to the body in a sub-healthy state (Sugiharto 2016;Jha et al 2019). The specific mechanism needs further research.…”
Section: Discussionmentioning
confidence: 93%
“…Among the nutrient supplements, arginine (Arg) is an essential amino acid for gestating mammals and crucial for intestinal development and neonatal growth [1,10], and markedly increased demands for Arg was observed in pregnancy [11]. Besides, Arg has been applied for the optimal development of the GIT as one of the essential amino acids in poultry [12][13][14]. Arg is well-known for the physiological and biomedical functions via its metabolites such as nitric oxide (NO) or polyamine [10].…”
Section: Introductionmentioning
confidence: 99%
“…December 2019 | Volume 7 | Issue 4 | Page 128 biota, enhanced immunity, and overall improved growth performance ( Jha et al, 2019). The injection materials have included vaccines, drugs, hormones and supplemental nutrients (Kadam et al, 2013).…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 99%